2000
DOI: 10.2307/2648271
|View full text |Cite
|
Sign up to set email alerts
|

Consistency of Self-Reports of Sexual Activity among Young Adolescents in Jamaica

Abstract: Context: Adolescents' sexual behavior is an important issue in developing countries and a focus of programmatic efforts for reducing pregnancy and sexually transmitted disease. Yet the accuracy of young people's reports of their sexual activity has rarely been carefully examined. Methods: Data from a three-round longitudinal study of 698 young adolescents in Jamaica were used to examine consistency in the reporting of first sexual intercourse. Adolescents were asked to respond to multiple questions about their… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
40
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(43 citation statements)
references
References 5 publications
(1 reference statement)
2
40
1
Order By: Relevance
“…In self-reported data based on recall, there is always the possibility that responses may have been minimized or inflated by the participants. 42 The measurement of religiosity was limited to items in the dataset. Important aspects of religiosity, such as faith, intrinsic religiosity, and religious well-being, were not assessed; thus, the nature of this construct was not fully captured.…”
Section: Limitationsmentioning
confidence: 99%
“…In self-reported data based on recall, there is always the possibility that responses may have been minimized or inflated by the participants. 42 The measurement of religiosity was limited to items in the dataset. Important aspects of religiosity, such as faith, intrinsic religiosity, and religious well-being, were not assessed; thus, the nature of this construct was not fully captured.…”
Section: Limitationsmentioning
confidence: 99%
“…For example, the majority (95%–100%) of 11-year-old to 14-year-old adolescents in Jamaica responded consistently about first sexual intercourse within each given survey round. However, across three waves of surveys, 37% of respondents—12% of girls and 65% of boys—responded inconsistently about the timing of their sexual debut 17. In a Kenyan study of adolescents aged 12–19 years (49% of whom were sexually active), 20% gave inconsistent reports about lifetime sexual intercourse and timing of first sexual intercourse,16 and in South Africa, 40% of sexually active adolescents inconsistently reported lifetime sexual experience 18…”
Section: Introductionmentioning
confidence: 99%
“…Self reports were the only method of assessment. Eggleston et al [34] observed that adolescents are not always truthful when providing self reports. Participants were informed that individual responses to the questions would be kept con�dential and would not be shared with classmates, parents, or school authorities.…”
Section: Strengths and Limitationsmentioning
confidence: 99%